Locally driven interannual variability of near‐surface pH and ΩA in the Strait of Georgia. Issue 3 (6th March 2016) - Moore‐Maley, Ben L.; Allen, Susan E.; Ianson, Debby
Abstract: Declines in mean ocean pH and aragonite saturation state (Ω A ) driven by anthropogenic CO2 emissions have raised concerns regarding the trends of pH and Ω A in estuaries. Low pH and Ω A can be harmful to a variety of marine organisms, especially those with calcium carbonate shells, and so may threaten the productive ecosystems and commercial fisheries found in many estuarine environments. The Strait of Georgia is a large, temperate, productive estuarine system with numerous wild and aquaculture shellfish and finfish populations. We determine the seasonality and variability of near‐surface pH and Ω A in the Strait using a one‐dimensional, biophysical, mixing layer model. We further evaluate the sensitivity of these quantities to local wind, freshwater, and cloud forcing by running the model over a wide range of scenarios using 12 years of observations. Near‐surface pH and Ω A demonstrate strong seasonal cycles characterized by low pH, aragonite‐undersaturated waters in winter and high pH, aragonite‐supersaturated waters in summer. The aragonite saturation horizon generally lies at ∼20 m depth except in winter and during strong Fraser River freshets when it shoals to the surface. Periods of strong interannual variability in pH and aragonite saturation horizon depth arise in spring and summer. We determine that at different times of year, each of wind speed, freshwater flux, and cloud fraction are the dominant drivers of this variability. These results establish the mechanisms behind the emerging observations of highly variable near‐surface carbonate chemistry in the Strait. Key Points: pH and aragonite saturation state demonstrate robust seasonal cycles Local physics and biology drive interannual pH and aragonite saturation state variability New mechanisms provide context to emerging pH and aragonite saturation state observations